Resgate de autoria em esquemas de assinatura em anel - Tomaz, Antonio Emerson Barros (2014)
The proposal presented in this thesis represents an expansion of the original concept of ring signature. A ring signature scheme allows a member of a group to publish a message anonymously, so that each member of the group can be considered the author of the message. The main idea of a ring signature is to guarantee the anonymity of the subscriber also ensure the authenticity of information, showing that the message came from one of the members of that group. This thesis presents a signature scheme based on (RIVEST et al., 2001), where the subscriber can later revoke anonymity presenting secret values that prove that he would only be able to generate such a signature. This property will be referred to here as rescue of authorship. The main difference to the proposal of Rivest et al. (2001) is presented before we even begin signature generation. The values used as input to the trapdoor function are message authentication codes - MACs generated by the HMAC algorithm, an algorithm for message authentication based on hash function collision resistant. This simple modification will allow, in the future, the subscriber to reveal itself as the true author of the message by showing the secret values to generate those MACs.